Knowledge and barriers to screening for colorectal cancer among individuals aged 40 years or older visiting primary healthcare clinics in Al-Khobar, Eastern Province - Assim M. Alabdulkader; Tajammal Mustafa; Danah A. Almutailiq; Razan A. Al-Maghrabi; Rabab H. Alzanadi; Danyah S. Almohsen; Nourah K. Alkaltham (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Colorectal cancer (CRC) ranks third as the most common cancer in the world and the 4th most common cause of deaths from cancer. In Saudi Arabia, CRC is the most common cancer in males and the third most common in females. Early screening reduces the risk of CRC and death. However, there is a lack of awareness of CRC screening in Saudi Arabia. The objective of this study was to determine the knowledge, practices, and barriers to CRC screening using the Health Belief Model (HBM). MATERIALS AND METHODS: This study enrolled Saudis aged 40 years or older visiting PHCCs in Al-Khobar. Data were collected using a self-administered questionnaire or a direct interview of the selected participants. Information sought included sociodemographics, past CRC screening, CRC knowledge, and HBM items. Data analysis was done using SPSS; the Chi-squared test and ANOVA were used to determine statistical significance. RESULTS: A total of 206 of the individuals approached completed the questionnaire. The average age was 51.1 years, and 51% were males. Only 10% reported that a physician had provided information on CRC prevention or discussed/recommended screening for CRC, and 10% had undergone screening for CRC. Seventy-five percent of respondents had heard of CRC, and 74% said that CRC was preventable. Regarding the HBM, no significant difference in the mean scores for perceived susceptibility, perceived severity, self-efficacy, and benefits of CRC screening was found by age groups. The mean score for perceived severity was higher for females than males. About 60% of participants were extremely likely to have a screening test for CRC done on the day if recommended by the doctor. CONCLUSION: The knowledge and awareness of CRC screening of the targeted sample is inadequate. Individuals with higher perceived susceptibility, severity of CRC, and perceived benefit of the screening tests were more willing to undergo the test. The highest perceived barrier was having no symptoms, and the lowest was "getting a stool test is too much of a hassle." These findings underline the importance of having a national screening program and campaigns to deal with the concerns of people and raise awareness of CRC.